A study on syntactic and semantic features of English physical appearance adjectives with reference to their Vietnamese equivalents : Luận văn. Chuyên ngành: NNA / Nguyen Minh Phuong; GVHD: Tran Thi Thu Hien - Nguyen, Minh Phuong
My graduation thesis namely “A study on syntactic and semantic features of English physical appearance adjectives with reference to their Vietnamese equivalents” is an investigation of the syntactic and semantic features of English physical adjectives, and from that results, the author refers these characteristics to their Vietnamese equivalents. The thesis fills a gap in the system of language works as there hasnot got a study working on the syntactic and semantic features of English physical appearance adjectives before. With the aim of providing a general and deeper view of English physical appearance adjectives for English learners as a foreign language in Vietnam, the thesis is carried out. The research as its name mentions, is not a contrastive analysis. After finding out the syntactic and semantic features of English physical appearance, the author refers to the Vietnamese equivalents to find out the similarities and differences between the two languages. In order to achieve the aims given, there are some methods are employed during the process of studying. Descriptive method seems to be the major with others as the quanlitative analysis, comparative and contrastive methods are the supporting methods. The English data sources of the study are collected from the famous novels and storiesin English and Vietnamese. The most important result of the study is finding out the similarities and differences in terms of syntactic and semantic features. In the limitation of the study, the author also mentions some typical idioms denoting people physical appearance and refers them to their Vietnamese equivalents in terms of semantic feature. From that result, the author suggests some implications using in teaching English adjectives denoting people appearance.